Avalia????o ambiental nos hot??is de Bras??lia selecionados pela FIFA para a Copa de 2014 - Neves, Maial?? Ferreira (2012)
In 2014 Brazil will host the FIFA World Cup and Brasilia is one of the cities chosen to receive this mega sport event. Events like this, large scale and international repercussion, have great economic potential, but also generate environmental impacts. This study aimed to evaluate the environmental initiatives implemented in FIFA selected hotels in host city Bras??lia, focusing on reducing water and energy consumption and solid waste generation and checking how the hotels are being prepared for the 2014 "Green Cup". For this, a research was conducted by means of literature and surveys in 18 of the FIFA-accredited hotels for 2014 World Cup checking if hotels have environmental or sustainability certifications and if they accomplish environmental actions of consumption management of water, energy and solid waste in order to improve their environmental performance. As a result of the research it was found that most hotels do not have environmental certification, however most of them had good or very good environmental performance regarding environmental actions implemented focusing on reducing water and energy consumption and solid waste generation. It was concluded that these are performed in most hotels, but in isolation and with few environmental action planning.